Analysis of Cutting System Failure in the CNC Vertical Machining Center of Hyundai Wia F500D Machine with the Root Cause Method at PT ABC - Wijaya, Raihan Rama; Nugraha, Asep Erik; Sumitra, Naufal Rabbani (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
PT ABC as an automotive component manufacturing company faces the problem of high Downtime in CNC machines, especially the Hyundai Wia F500D Vertical Machining Center, which has an impact on decreased productivity and increased production costs. This study aims to identify the root cause of the failure of the cutting system in the machine and provide recommendations for appropriate repairs. The method used is Root Cause Analysis (RCA) with the Fishbone Diagram approach and 5 Why's analysis based on historical company data, field observations, interviews with related parties, and technical documentation. The results of the study show that the dominant root cause of cutting system failure is damage to the drawbar disspring which reduces the grip strength of the tool so that it triggers the condition of the tool oblique, spindle overload, and active system alarm. Other causative factors include production methods with aggressive cutting parameters, operator errors in tool installation and maintenance, machine age that has been more than 12 years with almost non-stop operation, and a less ergonomic working environment. These conditions have an impact on increasing the frequency of repairs, maintenance costs, decreased production output, and high potential product defects. The conclusion of this study is the need for corrective actions in the form of replacing drawbar dissprings and repairing spindle components, as well as preventive measures through scheduled maintenance, optimization of production methods, improvement of operator competence, and improvement of the layout of the work area.